Cognitive, Structural, and Behaviour: The Deadlocked Situation in The Negotiation for Resolving Conflict Between Russia and Ukraine (2022-2025) - Dedi Yusuf; R. Widya Setiabudi Sumadinata; Akim (Yayasan Ilomata, 2026)
This paper examines recent negotiations regarding the conflict between Russia and Ukraine. The conflict escalated into a full-scale war in 2022 following Russia’s invasion of Ukraine. Using qualitative descriptive study and document analysis using Faure’s deadlock framework, this research identifies several indicators which show the negotiation between Russia and Ukraine for resolving their conflict has reached a deadlocked situation. This research also found that several factors such as cognitive, structural, and behavioural factor is causing the deadlock within the negotiations. The findings suggest that these factors are creating a condition where no substantive result and repeated arguments happened, which is indicators that the negotiation has reached a deadlocked condition. These findings also give implications towards the negotiation dynamics between two party, suggesting several strategies needed to overcome the deadlock within the negotiations. This research contributes to the limited amount of discourse regarding the negotiation conditions that occurred between Russia and Ukraine for resolving their conflict, offering a new perspective by applying Faure’s indicators and factors such as Cognitive, Structural, and Behaviour towards this issue.